SARS-CoV-2 seroprevalence study in Lambayeque, Peru. June–July 2020 - Díaz Vélez, Cristian (2021)
Background: Estimating the cumulative prevalence of SARS-COV-2 will help to understand the epidemic, contagion, and immunity to COVID-19 in vulnerable populations. The objective is to determine the extent of infection in the general population and the cumulative incidence by age group. Methods: It was carried out with a longitudinal analytical study, in the population of the Lambayeque region, located in the north of Peru. The selection was carried out in multistages (districts, area, household, and finally choosing the interviewee within the house). Seroprevalence was estimated as a positive result of the rapid test whether it was positive IgM or positive IgG. An adjustment was made for the sampling weights used. Results: The seroprevalence found in the region was 29.5%. Young people between 21 and 50 years old presented the highest seroprevalence frequencies. A total of 25.4% were asymptomatic. The most frequent complaint was dysgeusia and dysosmia (85.3% and 83.6%). Dysosmia (PR = 1.69), chest pain (PR = 1.49), back pain (PR = 1.45), cough (PR = 1.44), fever (PR = 1.41), general malaise (PR = 1.27) were associated factors with the higher the frequency of seropositivity for SARS-CoV-2. Reporting of complete isolation at home decreased the frequency of positivity (PR = 0.80), however, reporting having ARI contact (PR = 1.60), having contact with a confirmed case (PR = 1.51), and going to market (PR = 1.26) increased the frequency of positivity for SARS-CoV-2. Conclusion: These results suggest that Lambayeque is the region with the highest seroprevalence in the world, well above Spain, the United States and similar to a study in India.